ANALISIS PENGARUH LOCUS OF CONTROL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR (Studi Pada Badan Pemeriksa Keuangan Perwakilan Provinsi Jawa Timur) - Tri Maryanti; Endah Susilowati (Behavioral Accounting Journal, 2021)
This research was conducted to determine the effect of locus of control and leadership style on the performance of BPK auditors at the Representative Office of East Java Province. The results of research with the path coefficent Smart PLS test analysis state that locus of control has a significant effect on auditor performance and leadership style also has a significant effect on the performance of BPK auditors at the Representative Office of East Java Province. The result of R-Square (R2) auditor performance is 0.96, which means that the percentage of the influence of locus of control and leadership style on auditor performance is 96%, while the remaining 4% is explained by other variables.